Validation of a virtual forward simulation tool for ADAS assessment - Michelangelo-Santo Gulino; Giulio Vichi; Dario Vangi (European Transport Research Review)
Abstract As the adoption of active safety systems in road vehicles increases, there is a need for quantitative tools to evaluate the performance of Advanced Driver Assistance Systems (ADAS) aimed at collision mitigation. This paper introduces a Virtual Forward Simulation (VFS) tool that assesses ADAS performance by estimating Injury Risk for occupants involved in conflict situations. Established Injury Risk curves for impacts involving passenger cars are derived as a function of the vehicle’s velocity change during the impact ( $$Δ V$$ Δ V ). The paper provides a thorough validation of the proposed tool by comparing $$Δ V$$ Δ V from real-world accidents (or crash tests) with those obtained by simulations using a reduced-order impact model that underpins the VFS. Additionally, the $$Δ V$$ Δ V from simulations are compared with another VFS assessment tool available from the literature. The validation of the proposed VFS tool is further supported by comparing real and simulated deformed shapes of the vehicles. Results indicate that the proposed tool reliably replicates real accidents or crash tests, both quantitatively (in terms of $$Δ V$$ Δ V ) and qualitatively (in terms of deformations). The impact simulation algorithms implemented in the validated VFS tool provide an effective trade-off between high accuracy typical of finite element analysis and low computational costs typical of momentum-based models.